Measurement of harmonic distortion and Skewness of stator current of induction motor at crawling in Clarke plane. Issue 6 (1st November 2014) - Chattopadhyay, Surajit; Chattopadhyaya, Aveek; Sengupta, Samarjit
Abstract : This study deals with measurement of harmonic distortion and Skewness of stator current in Clarke plane at crawling of induction motor. Three‐phase current signals have been transformed into Clarke plane. Dominancy of seventh harmonic is observed by assessing maxima and minima of stator current Concordia in Clarke plane. Specific reference signals having sinusoidal nature and different frequencies are defined and then areas covered by the real system data with the reference signal have been determined, wherefrom individual contributions of fundamental waveform and harmonic components are measured separately and total harmonic distortion factors are determined. Then wavelet decomposition of stator current is done in Clarke plane, wherefrom, signals are assessed with the help of Skewness of approximate coefficient in Clarke plane. Significant differences are noted between those parameters found during crawling and that of normal condition which may be useful in detection of such fault.